Sosialisasi Pembuatan Concrete Block dan Bata Beton Dengan Teknologi Pencampuran Beton Berbasis Slag Nikel di Desa Tambea - Dzakir, La Ode; Mansyur; Adnan, Septi; La Ode, Al Tafakur; Simatupang, Minson; Edwin, Romy Suryaningrat; Tamburaka, Irmawatti Paula (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
Nickel slag is a by-product of the nickel ore smelting process and can be used as an alternative to cement and fine aggregates. This community service program aims to develop and apply concrete mixing technology based on nickel slag as an environmentally friendly alternative material for producing concrete blocks and concrete brick in Tambea Village. The community, which is engaged in small-scale construction businesses, is involved in this training. The investigation results indicate that the community gained a better understanding of how to use industrial waste and produce high-quality nickel slag-based concrete. This project is expected to enhance the local economy by implementing sustainable technology based on local materials.